Nilai-Nilai Dakwah Islamiyah Pada Novel Api Tauhid Karya Habiburrahman El Shirazy: Kajian Struktural Genetik - Fauziah Suparman (UHAMKA Graduate School Thesis Abstract Collection, 2016)
This research aims to find the Islamic da’wah values in Api Tauhid novel by Habiburrahman El Shirazy using genetic structural study. This research is qualitative research using content analysis technique. The researcher found the correlations between the content of the novel with the author's life. First, the characters of Hamza and Bilal who know the biography of a remarkable scholar Bediuzzaman Said Nursi in very detail, so that in the story they are able to tell Bediuzzaman Said Nursi’s struggle coherently. Secondly, the depiction of the characters in the novel are very religious, especially the main character, Fahmi. Religious background is created no other than the madrasah he had to take, after which he was studying at boarding schools, and finally he was enrolled to study religion in the Middle Eastern country. Third, the story when Fahmi invited by his friend, Hamza (the Turks) to get around Turkey in memory of the history of the struggle of Bediuzzaman Said Nursi. Fourth, it is told in the novel about the Fahmi, Hamza and his friends’ trip in Turkey. They visited various places that become the traces of the history of Islam and the struggle of Bediuzzaman Said Nursi. Based on the above correlation explained above, the author in his work cannot be separated from the circumstances of the surrounding community. In this case, the characteristics, ideological, political, economic, and social culture's influence on this Habiburrahman’s work. Social culture that is attached to a work can be viewed from several aspects, such as: social culture, language, religion, employment, customs, arts, and others. The implication of this research is the implementation or application in High School which is expected to have a positive impact on students after studying the literature teaching topic. Api Tauhid novel may be one of the sources of teaching Indonesian subject for High School class XII in the second semester.